(untitled) (Research, Society and Development, 2021)
The water use by the corn crop is apparently closely related to the levels of phosphorus available in the soil. The objective of this work was to evaluate the effect of irrigation frequency combined with different doses of phosphate fertilizer on the biometric characteristics of the corn crop under two planting densities. The experiment was installed in a scheme of subdivided plots. In the main plot, seven irrigation frequencies and two plant populations. In the sub-subplots, five doses of phosphorus. The population of 80 thousand plants ha-1 showed higher plant height and ear insertion, regardless of the irrigation shift adopted and the dose of phosphorus applied. The population of 60 thousand plants ha-1, showed a greater length of ears, number of grains in the row and a mass of 1000 grains. Increasing doses of phosphorus, affected plant heights and ear insertion height in the population of 60 thousand plants ha-1. As for the population of 80 thousand plants ha-1, increasing doses of phosphorus affected stem diameter. There was no effect of phosphate fertilization on the productive characteristics studied: harvest index, ear diameter, ear length, number of grain rows, number of grains in the row and mass of 1000 grains.